1970
DOI: 10.1038/227959a0
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Flexibility in Drosophila melanogaster

Abstract: SMALL SPOT IN CENTRE RESPONSE}'il- (. 4. Receptive field org,tnization of a ganglion cell of the isolated rat retina. A single unit was found which showed centre surround organization. A diffuse stimulus produced an on response in this cell. A small spot presented in the region of the recording microelectrode produced an off response. An annular stimulus or a slightly eccentric spot produced an on-off response.of the preparation. Another explanation might be that of sampling error. ~-e know of no way to resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
2
4

Year Published

1975
1975
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(134 citation statements)
references
References 13 publications
7
114
2
4
Order By: Relevance
“…This difference is also shown in other populations of Drosophila melanogaster (Gibson, 1970;Ward, 1975;Oakeshott, 1976). Genetical variation for ADH activity in the "Texas" population is also manifest amongst lines of the same electromorph, indeed there is about a two-fold difference between the highest and lowest ADH activities whether the flies are of the AdhS'S or Adh' genotype Birley and Barnes 1975).…”
Section: Dxscussiosupporting
confidence: 53%
See 1 more Smart Citation
“…This difference is also shown in other populations of Drosophila melanogaster (Gibson, 1970;Ward, 1975;Oakeshott, 1976). Genetical variation for ADH activity in the "Texas" population is also manifest amongst lines of the same electromorph, indeed there is about a two-fold difference between the highest and lowest ADH activities whether the flies are of the AdhS'S or Adh' genotype Birley and Barnes 1975).…”
Section: Dxscussiosupporting
confidence: 53%
“…the difference between ADH-F and ADH-S is adaptive in the presence of alcoholic substrates in the food medium (Gibson 1970;Bijlsma-Meeles and Van Delden, 1974;Briscoe, Robertson and Malpica, 1975;Morgan, 1975;Oakeshott, 1976) and can be attributed to the catalytic efficiencies of these enzymes (Day, Hillier and Clarke, 1974;Clarke, 1975). The causes and adaptive strategies for the genetical variation at modifier loci are less well understood and may well be manifold.…”
Section: Dxscussiomentioning
confidence: 99%
“…We think it unsafe to draw allele homologies between the allele types in the island and continental forms since the most commonly occurring allele in the widely-separated geographic populations may not be the same. Gibson (1970) has provided evidence why we might expect to see differences in allele frequencies at this locus. Vigue and Johnson (1973) have demonstrated significant differences in allele frequencies which demonstrate a North-South cline.…”
Section: Drosophila Simulans Variabilitymentioning
confidence: 99%
“…Several multi-generation experiments have suggested that F, which produces at least twice the ADH activity of S, reaches higher equilibrium frequencies in populations kept on ethanol impregnated food than in those kept on food without added ethanol (van Delden, 1982 for a review). But once again the total experimental results are ambiguous; Gibson and Oakeshott (1982) have pointed out that higher F frequencies have generally only been obtained with populations which have spent at least a year in the laboratory prior to the experiment (Gibson, 1970;Bijlsma-Meeles and van Delden, 1974;van Delden eta!., 1978;Oakeshott, 1979;Cavener and Clegg, 1981;Vigue et a!., 1982).…”
Section: Introductionmentioning
confidence: 99%